2005
DOI: 10.1186/1744-859x-4-19
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors associated with mental illness in Oyo State, Nigeria: A Community based study

Abstract: Background: The main objective of this study was to determine the prevalence and factors associated with mental illness in Oyo State at community level using the general health questionnaire as a screening tool.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
8
6

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 14 publications
8
8
6
Order By: Relevance
“…This finding was consistent with previous studies conducted in Kenya (11%) [ 15 ], Borena Southern Ethiopia (14.6%) [ 16 ] and Addis Ababa (11.7%) [ 17 ]. But our finding was lower than many of the previous studies that reported prevalence of CMI among study population 21.9% in Nigeria [ 13 ], 22.7% in Jimma Ethiopia [ 18 ], 24.6% in Britain [ 19 ], 25.5% in Chile, Santiago [ 20 ], 27-30% in south Africa [ 21 , 22 ], 29.9% in Brazil [ 14 ] and 30.3% in Britain [ 21 ].…”
Section: Discussioncontrasting
confidence: 87%
See 1 more Smart Citation
“…This finding was consistent with previous studies conducted in Kenya (11%) [ 15 ], Borena Southern Ethiopia (14.6%) [ 16 ] and Addis Ababa (11.7%) [ 17 ]. But our finding was lower than many of the previous studies that reported prevalence of CMI among study population 21.9% in Nigeria [ 13 ], 22.7% in Jimma Ethiopia [ 18 ], 24.6% in Britain [ 19 ], 25.5% in Chile, Santiago [ 20 ], 27-30% in south Africa [ 21 , 22 ], 29.9% in Brazil [ 14 ] and 30.3% in Britain [ 21 ].…”
Section: Discussioncontrasting
confidence: 87%
“…Sample size determination and sampling procedure : The sample size was determined by two proportion formula considering the study which was conducted in Oyo state of Nigeria [ 13 ]. The proportion of the psychiatric morbidities among urban and rural area were 18.4% and 28.4%, respectively.With a precision of 95% and the desired power of 80%.…”
Section: Methodsmentioning
confidence: 99%
“…[16] From community samples in Nigeria, rates of 19.2% to 28.5% have also been reported. [16,17,18] The findings that infertility is associated with severe psychological distress are in agreement with previous studies. [19,20,21,22] The predictors of severe psychological distress in this study were not having at least one child, financial burden of treatment, duration of infertility, stressed by infertility, and marital instability due to infertility.…”
Section: Discussionsupporting
confidence: 91%
“…Many studies (e.g., Amoran et al, 2005;Abdallah and Ogbeide, 2002) have concluded that a higher rate of mental illness exists among the widowed than their married counterparts. Even a study conducted by Chen et al, (1999) concluded that widows had higher mean levels of traumatic grief, depressive and anxiety symptoms (compared to widowers).…”
Section: Widowhood and Its Psychological Aspectsmentioning
confidence: 98%